2012
DOI: 10.1186/1472-6939-13-34
|View full text |Cite
|
Sign up to set email alerts
|

Review of national research ethics regulations and guidelines in Middle Eastern Arab countries

Abstract: BackgroundResearch ethics guidelines are essential for conducting medical research. Recently, numerous attempts have been made to establish national clinical research documents in the countries of the Middle East. This article analyzes these documents.MethodsThirteen Arab countries in the Middle East were explored for available national codes, regulations, and guidelines concerning research ethics, and 10 documents from eight countries were found. We studied these documents, considering the ethical principles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
98
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 8 publications
2
98
0
Order By: Relevance
“…32 Although our study was conducted in a Muslim country, the highly positive attitude of respondents contrasts with fatwa 67 (1992) …”
Section: Trends In Attitudes Toward Pediatric Researchmentioning
confidence: 90%
“…32 Although our study was conducted in a Muslim country, the highly positive attitude of respondents contrasts with fatwa 67 (1992) …”
Section: Trends In Attitudes Toward Pediatric Researchmentioning
confidence: 90%
“…Ethical regulations in many Arab institutions are deficient in many aspects, particularly in relation to development, structure, content, and reference to international ethical guidelines. [17] Despite obvious defects of citation practices, [18] some Arab institutions spend a lot of money to lure "highly cited authors" or to coaffiliate their published papers with institutions abroad to appear with more "prestige" or "excellence" in biased ranking systems such as the Shanghai ranking [19,20] or alike. It is, however, not a question of citations but the utility of manuscripts in real life to bring concrete solutions to health, technical, or environmental challenges.…”
mentioning
confidence: 99%
“…4 It has been observed that, "Many factors make the Middle East attractive for clinical research, including the diversity of its patients, good medical facilities, cost advantages, and favorable infrastructure-especially in the Persian Gulf countries." (Alahmad, Al-Jumah, and Dierickx 2012) It has been noted that "with countries in the Middle East operating under considerably fewer strict ethical guidelines, than their European and North American counterparts, drugs companies are increasingly moving trials of new and untested drugs to Arab countries." (Alahmad et al 2012) The purpose of this paper is: (a) to inquire into the ethical rules, principles and norms that apply to human experimentation; and (b) to address the issue of when does human experimentation become a form of human trafficking, giving rise to criminal liability of medical doctors.…”
mentioning
confidence: 99%
“…(Alahmad, Al-Jumah, and Dierickx 2012) It has been noted that "with countries in the Middle East operating under considerably fewer strict ethical guidelines, than their European and North American counterparts, drugs companies are increasingly moving trials of new and untested drugs to Arab countries." (Alahmad et al 2012) The purpose of this paper is: (a) to inquire into the ethical rules, principles and norms that apply to human experimentation; and (b) to address the issue of when does human experimentation become a form of human trafficking, giving rise to criminal liability of medical doctors. A case of medical experimentation, in addition to being in violation of ethical standards, may also give rise to the crime of human trafficking.…”
mentioning
confidence: 99%
See 1 more Smart Citation